Thequantity of Streptococcus mutancolonyin breastfeedandformula milk infant (Jumlah koloni Streptococcus mutan pada bayi peminum air susu ibu dan peminum susu formula) - Ridhayani Hatta; Hendrastuti Handayani (DiscoverSys Inc., 2014)
Caries in infant was influenced by their substrat. Substrats are the primary source of energy in bacterial colonisingprocess in oral cavity. Streptococcus mutans are especially the main cause of tooth decay. For 1-year-old infant theprimary nutritions are generally from breast milk or formula milk. This study was aimed to determine the differentnumbers of bacterial colonizations of S.mutan found in breast-fed infants from those found in formula milk. Thisobservational-analytics study used cross sectional study design was carried out to 60 infants who fulfil the inclutioncriteria of simple random sampling method,30 infants in each group from Integrated Health Centre in Kelurahan Antang,and the bactery on the saliva was evaluated in Microbiology Laboratory of Medical Faculty Hasanuddin University. Eachparent was given questionnaire which to asks the things related with this research and microbial screening was takenfrom saliva of 1-year old infant. The number of bacterial colonizations for S.mutans in breastfeeding group shows meanvalue 19.7 CFU/ml while the formula milk group was about 37.97 CFU/ml, so the consumptions of breast milk andformula milk in 1-year old infant show the significantly different number of bacterial colonizations of S.mutans in. Itwas concluded that colonization of S.mutans in breastfeeding group lower than formula milk group.